Gangs and environment: a comparative analysis of prison and street gangs - Ortiz, Jennifer M. (American journal of qualitative research, 2018)
One misconception in gang research is the assumption that prison gangs and street gangs are organizationally and ideologically synonymous. Although in the minority, some researchers suggest that prison gangs are qualitatively and quantitatively different from other gangs (Fleisher & Decker, 2001). Utilizing 30 in-depth semi-structured interviews with formerly incarcerated gang members in the New England area, this article assesses the effect of environment on the organizational structure, ideologies, and practices of prison and street gangs. The analysis presents a comparative model of prison and street gangs that highlights differences across major aspects of each type of organization, including membership, leadership, organizational operations, and relationships with authority figures. These findings suggest a need for researchers to explore prison and street gangs as distinct entities each affected by their respective environments. Policy suggestions and directions for future research are discussed.